Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702608
|View full text |Cite
|
Sign up to set email alerts
|

How Deceptive are Deceptive Visualizations?

Abstract: In this paper, we present an empirical analysis of deceptive visualizations. We start with an in-depth analysis of what deception means in the context of data visualization, and categorize deceptive visualizations based on the type of deception they lead to. We identify popular distortion techniques and the type of visualizations those distortions can be applied to, and formalize why deception occurs with those distortions. We create four deceptive visualizations using the selected distortion techniques, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 24 publications
5
55
1
Order By: Relevance
“…This holds true across varying amounts of data shown in the graphs, as there were only two data points in the bar and bubble graphs, seven in the pie, and eleven in the line graph. These results confirm Pandey et al [5] and O'Brien & Lauer [3], while extending those studies to show deceptiveness in the new genres of a line graph with a truncated axis and a pie graph with a 3D bevel effect.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This holds true across varying amounts of data shown in the graphs, as there were only two data points in the bar and bubble graphs, seven in the pie, and eleven in the line graph. These results confirm Pandey et al [5] and O'Brien & Lauer [3], while extending those studies to show deceptiveness in the new genres of a line graph with a truncated axis and a pie graph with a 3D bevel effect.…”
Section: Resultssupporting
confidence: 89%
“…Only recently have scientists started to empirically test the extent to which people are actually deceived by deceptive tactics used in data visualizations [3-5, 21, 25]. Pandey et al was the first to empirically show that participants were more likely to be misled in their interpretations of data visualizations that employed deceptive tactics such as message reversal (e.g., an inverted axis) and message exaggeration (e.g., truncated y-axis) [5]. Following this, O'Brien and Lauer found that people's perception of information presented in deceptive data visualizations persisted even when the deceptive graphic was paired with a paragraph of accurate text [3].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] states that the model prefers to include zero for continuous fields and that violating the rule increases the cost of the visualization by 5. A soft constraint is appropriate: though omitting a zero baseline for ratio data can mislead [42], it is still sometimes reasonable to do. Note that a visualization may violate a soft constraint multiple times.…”
Section: Preference Over the Design Spacementioning
confidence: 99%
“…Visualization designers benefit from familiarity with both the data domain under consideration and principles of effective visual encoding. Although designers can learn these principles from books, research papers, and experience, they do not always follow these principles in practice [6,42]. Automated design tools [37,66] are designed to help address this problem: they use formally-encoded design guidelines to promote effective visualizations.…”
Section: Introductionmentioning
confidence: 99%